Using vignette methodology to research the process of breach comparatively. (December 2015) - Maguire, Niamh; Beyens, Kristel; Boone, Miranda; Laurinavicius, Alfredas; Persson, Anders
Comparative research related to any aspect of the process of breach in either the pre-trial, sentencing or release phases is relatively rare. Comparative studies of decision making in the specific context of breach process are particularly lacking. One reason for the dearth of research in this area is the many challenges presented by comparative research across different jurisdictions. This article focuses on the development of a vignette methodology to explore the decision-making aspect of the breach process from a comparative perspective across a number of different European jurisdictions. The vignettes are designed to explore the decision-making aspects of two different types of breach process – the process of breach that follows on from a breach of conditions of early release from prison and the process that follows a breach of conditions attached to the completion of an unpaid work order. The article begins by contextualizing the research in debates about the relationship between compliance, legitimacy and rising prison populations. It critically examines the nature of vignette methodology and then discusses the specific challenges of using vignettes in comparative research as well as the development, piloting and evaluation of the decision-making vignettes in focus. We conclude by discussing some of the challenges we faced and particularly our challenge in terms of the development of the methodology – enhancing the comparability of the findings.